2019
DOI: 10.1016/j.cemconcomp.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the corrosion susceptibility of Recycled Steel Fiber Reinforced Concrete

Abstract: Steel fibers resulting from the industry of tire recycling can be efficiently employed in concrete to improve its mechanical performance, such as post-cracking load bearing and energy absorption capacity. Under chloride attack, an important aspect of Recycled Steel Fiber Reinforced Concrete (RSFRC) durability is its corrosion resistance. However, the insufficient knowledge on this domain contributes for a conservative design philosophy, which can compromise the cost competitiveness of RSFRC and prevent its app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 43 publications
(52 reference statements)
0
33
0
Order By: Relevance
“…3, which would drastically influence the crossing of fibres along crack openings and in turn result in significant variations in the bridging mechanism. RTSF with more irregular shape has higher possibility to be ruptured during fibre-bridging action owing to greater fibre pull-out load and the toughness properties would be accordingly influenced (Frazão et al, 2019).…”
Section: Flexural Toughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…3, which would drastically influence the crossing of fibres along crack openings and in turn result in significant variations in the bridging mechanism. RTSF with more irregular shape has higher possibility to be ruptured during fibre-bridging action owing to greater fibre pull-out load and the toughness properties would be accordingly influenced (Frazão et al, 2019).…”
Section: Flexural Toughnessmentioning
confidence: 99%
“…In recent years, recycled tyre steel fibre (RTSF) was introduced into cementitious materials to maximise the usage of recycled materials and further promote the sustainable development. The effect of RTSF on mechanical and durability performances of fibre reinforced concrete (FRC) has been extensively investigated (Aiello et al, 2009;Bjegovic et al, 2014;Centonze et al, 2012;Frazão et al, 2019;Grzymski et al, 2019;Neocleous et al, 2008;Skarżyński and Suchorzewski, 2018;Zamanzadeh et al, 2015). However, very limited study can be found in literature regarding the effect of RTSF on the properties of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several investigations have explored the potential of end-of-life tires by-products in the construction industry, such as the use of recycled steel fibers (RSFs) in the reinforcement of cement-based materials [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], namely, in fiber reinforced concrete (FRC). FRC is being used in slabs and shells, such as the case of flooring and tunneling since the support redundancy of this type of structure favors the occurrence of a high level of stress redistribution during crack propagation, which increases their ultimate load regarding their cracking load [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, RSFs show a high potential to be an effective concrete reinforcement for application in structural elements, namely, those that are exposed to coastal/marine environments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. However, research on the corrosion resistance of recycled steel fiber reinforced concrete (RSFRC) is almost non-existent, namely, concerning the effects of chloride attack on the fiber reinforcement mechanisms developed during the fiber pull-out from the matrix in cracked RSFRC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation